Association of P2X7 polymorphisms on Type 2 diabetes mellitus susceptibility and diabetic complications. - Guoni Huang; Jing Cheng; Wenfeng Liu; Tong Yang; Tao Ye; Qian Zhang; Qi Chen; Yuzhong Xu (PLoS ONE)
Objectives This case-control study aims to clarify the impact of single nucleotide polymorphisms (SNPs) within the P2X7 gene on susceptibility to type 2 diabetes mellitus (T2DM) and to evaluate their association with diabetic complications. Methods This study is comprised with 200 T2DM cases and 200 healthy controls. Seven candidate SNP loci were screened, and TaqMan-MGB real-time PCR technology was used to determine the polymorphic variants of P2X7. Different genotype and allele frequencies were compared by Pearson's χ2 tests and logistic regression analysis. Results Three P2X7 SNPs were found to be associated with T2DM risk. Specifically, rs7958311 GA (OR = 1.323, p = 0.002), rs7958311 AA (OR = 1.508, p = 0.038), rs208294 CC (OR = 1.854, p = 0.042) showed a higher susceptibility to T2DM, whilst rs11065464 CA (OR = 0.614, p = 0.022) was associated with a reduced risk. Logistic regression analysis indicated that rs7958311 was linked to an increased risk for nephropathy (OR = 1.833, p = 0.022), but with a decreased risk for peripheral artery disease (OR = 0.550, p = 0.042). Additionally, rs208294 was identified as a risk factor for peripheral neuropathy (OR = 2.101, p = 0.016). Conclusions We found that P2X7 polymorphisms are significantly associated with the risk of T2DM and its complications, suggesting that targeting P2X7 may offer a novel therapeutic strategy for the prevention and personal treatment of T2DM.